(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Background: Orthodontics is a dental specialty focused on the diagnosis, prevention, and management of malaligned teeth and craniofacial discrepancies, and prompting facial esthetics. The use of fixed orthodontic appliances, creates numerous retentive niches that predispose individuals to increased plaque accumulation and food debris retention. This, in turn complicates effective oral hygiene practices. Objective: The study’s objective is immunological evaluation of immunoglobulin A (IgA) and interleukin 26(IL-26) in white spot lesions in fixed orthodontic treatment. Material and method: A total of 100 individuals, including 50(50%) experimental and 50 (50%) controls, 36 males and 64 females, aged 15-35, underwent fixed orthodontic treatment for those measuring salivary biomarkers by ELISA for at least one month after appliance activation. Results: The findings showed that the case group had higher significant differences as opposed to the control group with p value = 0.002 regarding IgA, while IL-26 showed no significant difference between the two groups with p value 0.557. Conclusion: Compared to the control group, which exhibited no sign of white spot lesions, the case group demonstrated elevated levels of salivary IgA, while IL-26 levels remained relatively unchanged.